The impact of dieting culture is different between sexes in endurance athletes: a cross-sectional analysis - Austin J. Graybeal; Andreas Kreutzer; Jada L. Willis; Robyn Braun-Trocchio; Kamiah Moss; Meena Shah (BMC, 2022)
Abstract Background Frequent dieting is common in athletes attempting to achieve a body composition perceived to improve performance. Excessive dieting may indicate disordered eating (DE) behaviors and can result in clinical eating disorders. However, the current nutrition patterns that underly dieting culture are underexplored in endurance athletes. Therefore, the purpose of this study was to identify the sex differences in nutrition patterns among a group of endurance athletes. Methods Two-hundred and thirty-one endurance athletes (females = 124) completed a questionnaire regarding their dieting patterns and associated variables. Results The majority of athletes did not follow a planned diet (70.1%). For endurance athletes on planned diets (n = 69), males were more likely follow a balanced diet (p = 0.048) and females were more likely to follow a plant-based diet (p = 0.021). Female endurance athletes not on a planned diet (n = 162) were more likely to have attempted at least one diet (p < 0.001). Male athletes attempted 2.0 ± 1.3 different diets on average compared to 3.0 ± 2.0 for females (p = 0.002). Female athletes were more likely to attempt ≥ three diets (p = 0.022). The most common diet attempts included carbohydrate/energy restrictive, plant-based, and elimination diets. Females were more likely to attempt ketogenic (p = 0.047), low-carbohydrate (p = 0.002), and energy restricted diets (p = 0.010). Females made up the entirety of those who attempted gluten-/dairy-free diets (F = 22.0%, M = 0.0%). Conclusions Being a female athlete is a major determinant of higher dieting frequency and continual implementation of popular restrictive dietary interventions. Sports dietitians and coaches should prospectively assess eating behavior and provide appropriate programming, education, and monitoring of female endurance athletes.